Ultrasound Guided Percutaneous Nephrolithotomy in Mesh-Repaired Incisional Hernia - Seyed Hassan Inanloo; Mohammad Reza Nikoobakht; Hamed Akhavizadegan; Mojgan Karbakhsh (Advances in Urology)
Objectives. To describe our technique of percutaneous nephrolithotomy (PNL) in patients with mesh-repaired flank incisional hernia. Polypropylene mesh which is used for fascia strengthening in hernia repair elicits intense inflammatory reaction and the consequent fibrosis alters the characteristics of abdominal wall. Thus, prior history of flank hernia repair with mesh may result in percutaneous nephrolithotomy failure. Materials and Methods. Demographic data, renal stones characteristics, and any complication during surgery and follow-up of patients who were treated by PNL during 2011 to 2020 and had mesh in their flank region were collected. Results. Percutaneous nephrolithotomy was performed without any problem in 8 patients with guide of ultrasonography. Conclusion. Based on our experience, ultrasound-guided PNL is feasible and hypothetically superior to fluoroscopy in such circumstances.